Interaction, language practice, and the construction of the social universe - Goodwin, Marjorie Harness (Calidoscópio, 2021)
As a linguistic anthropologist my concern is to describe rigorously, systematically, and empirically the array of resources utilized by participants to build their ongoing social organization as the situated product of interactive practices. In the first part of this report I discus how we can integrate talk, intonation, the body, and the built environment into our analysis of language usage. An approach that combines analysis of talk in interaction with ethnography provides a more informed picture of girls’ lives than exists in either social science or popular literature. With this introduction to basic concepts of embodied action and situated activity system, in the second part of the paper I examine how the lived local social order is brought into being by investigating children interacting with parents in the midst of directive/response sequences (sequences in which parents are attempting to get their children to do something). The repetitive ways in which children and parents collaborate in the building of argumentative sequences I believe has consequences for how children, across a range of situations, develop negotiational skills. By looking closely at the type of order that is achieved, analysts can examine how moment-to-moment interaction is consequential for larger social processes. Key words: interaction, language practice, social processes.